2005
DOI: 10.1007/s10722-004-6896-0
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Microsatellites to Investigate the Origin of Grapevine

Abstract: The origin of the grapevine, Vitis vinifera L. (ssp.) sativa has been investigated with archaeobotanicalarchaeological, cultural and historical data indicating a unique domestication centre located in the Caucasian and Middel-East regions about 6-7000 years ago, but, events leading to the domestication of this species are still an open issue. In this work, eight universal chloroplast microsatellites are used to assess genetic relationships among varieties selected as representatives of four distinct geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 19 publications
7
52
0
3
Order By: Relevance
“…The results obtained reinforced the idea of Western Europe as one of the domestication centres for grapevines (Grassi et al 2003, Arroyo-Garcia et al 2006, with contributions from the Eastern gene pool (Imazio et al 2006). The observed genetic structure is a starting point to clarify the high number of native cultivars from Portugal, and it reinforces their probable origins on the Iberian Peninsula.…”
Section: S55supporting
confidence: 84%
“…The results obtained reinforced the idea of Western Europe as one of the domestication centres for grapevines (Grassi et al 2003, Arroyo-Garcia et al 2006, with contributions from the Eastern gene pool (Imazio et al 2006). The observed genetic structure is a starting point to clarify the high number of native cultivars from Portugal, and it reinforces their probable origins on the Iberian Peninsula.…”
Section: S55supporting
confidence: 84%
“…On the contrary, high H values were observed in groups Turkey (H = 0.533) and Iran (H = 0.378), although a relatively fewer accessions from these groups were analysed. These data showed that H increases from West to East in the Mediterranean basin, unlike what was observed in grapevine by Imazio et al (2005).…”
Section: Chlorotype Variation and Distribution In The Geographical Grmentioning
confidence: 49%
“…Thus in angiosperms the chloroplast genome can only be disseminated by seeds or cuttings. Chloroplast SSR (cpSSR) markers have been developed in recent years (Provan et al 2001) and have been used to investigate the origin and diffusion of several fruit tree species, such as grape (ArroyoGarcía et al 2002;Imazio et al 2005;Arroyo-García et al 2006) and olive (Breton et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…vinifera) carrying the alleles of hermaphroditism and berries size. Most probably these cultivars crossed with local wild vines giving rise to local cultivars (Wagner 1976;Imazio et al 2006). Similarities among local cultivars and wild vines are an outcome of these crosses.…”
Section: Introductionmentioning
confidence: 99%